2011
DOI: 10.1021/mp200313e
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies for Gaucher Disease: Miglustat (NB-DNJ) as a Pharmacological Chaperone for Glucocerebrosidase and the Different Thermostability of Velaglucerase Alfa and Imiglucerase

Abstract: Gaucher disease (GD) is a disorder of glycosphingolipid metabolism caused by deficiency of lysosomal glucocerebrosidase (GlcCerase) activity, due to conformationally or functionally defective variants, resulting in progressive deposition of glycosylceramide in macrophages. The glucose analogue, N-butyldeoxynojirimycin (NB-DNJ, miglustat), is an inhibitor of the ceramide-specific glycosyltransferase, which catalyzes the first step of glycosphingolipid biosynthesis and is currently approved for the oral treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 63 publications
0
29
0
1
Order By: Relevance
“…28,36 Miglustat is an imino sugar analog of glucose that is an inhibitor of glucosylceramide synthase. 28,38,42,46,47 Miglustat is currently the only FDA-approved SRT for Gaucher’s disease. Eliglustat tartrate is another SRT that is currently in phase III clinical trials after the completion of a successful phase II clinical trial.…”
Section: Gaucher’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…28,36 Miglustat is an imino sugar analog of glucose that is an inhibitor of glucosylceramide synthase. 28,38,42,46,47 Miglustat is currently the only FDA-approved SRT for Gaucher’s disease. Eliglustat tartrate is another SRT that is currently in phase III clinical trials after the completion of a successful phase II clinical trial.…”
Section: Gaucher’s Diseasementioning
confidence: 99%
“…47,50,51 Other therapeutic options have been or are being considered for Gaucher’s disease including bone marrow transplantation (for non-neurological Gaucher’s disease), gene therapy, and pharmacological chaperone therapy. 28,30,32,46,47,5052 Isofagomine tartrate is a pharmacological chaperone that was under recent pre-clinical development and was designed to bind to and help stabilize the misfolded glucocerebrosidase that arises from the specific N370S mutation. 52 However after initial clinical trials with minimal “clinically meaningful improvements,” further clinical development of isofagomine tartrate was discontinued (October 2, 2009 press release from Amicus Therapeutics).…”
Section: Gaucher’s Diseasementioning
confidence: 99%
“…Miglustat (Zavesca, N-butyl-deoxynojirimycin) is a drug developed by Actelion and used primarily to treat the lysosomal storage disease type 1 Gaucher disease. Miglustat is an imino sugar first synthesized by Butters and Dwek who found that N-alkylated analogs of the natural product deoxynojirimycin were inhibitors of the glucosyl-transferase involved in glucosylceramide biosynthesis (Abian et al, 2011; Platt et al, 1997). Treatment with miglustat was shown to alleviate the built up of sphingolipid seen in Gaucher disease.…”
Section: Engineered Glycans and Glycan Mimics As Therapeutic Agentsmentioning
confidence: 99%
“…For example, the effects of miglustat may be due to its modest effects as a glucosylceramide synthase inhibitor or rather be the result of chaperone effects resulting from its direct binding to GBA ( 39 ). Miglustat cocrystallizes with lysosomal glucocerebrosidase and its binding is greater at neutral compared with acidic pH ( 40 ).…”
Section: Downloaded Frommentioning
confidence: 99%